Association of donor age, body mass index, hemoglobin, and smoking status with in‐hospital mortality and length of stay among red blood cell–transfused recipients. Issue 11 (11th October 2019) - Roubinian, Nareg H.; Westlake, Matt; St. Lezin, Elizabeth M.; Edgren, Gustaf; Brambilla, Don J.; Lee, Catherine; Bruhn, Roberta; Cable, Ritchard G.; Triulzi, Darrell J.; Glynn, Simone A.; Kleinman, Steve; Murphy, Edward L.; et al.
Abstract : BACKGROUND: Recent publications have reported conflicting findings regarding associations of blood donor demographics and mortality of transfused patients. We hypothesized that the analysis of additional donor characteristics and consideration of alternative outcomes might provide insight into these disparate results. STUDY DESIGN AND METHODS: We analyzed data from a retrospective cohort of transfused patients from the Recipient Epidemiology and Donor Evaluation Study‐III (REDS‐III). We used stratified Cox regression models to estimate associations between blood donor characteristics and hospital mortality and posttransfusion length of stay among patients transfused red blood cell (RBC) units. Donor characteristics evaluated included age, body mass index, hemoglobin levels, and smoking status. The statistical analyses were adjusted for recipient factors, including total number of transfusions. RESULTS: We studied 93, 726 patients in 130, 381 hospitalizations during which 428, 461 RBC units were transfused. There were no associations between blood donor characteristics and hospital mortality. Receipt of RBC units from donors less than 20 years of age was associated with a shorter hospital length of stay (hazard ratio for discharge per transfused unit, 1.03; 95% confidence interval, 1.02‐1.04; p < 0.001) but not for other donor characteristics. CONCLUSION: We found no evidence of associations between blood donor factors and in‐hospital mortality. Our finding of shorter hospital length of stay in patients transfused RBCs from younger donors is intriguing but requires confirmation. Future collaborations are needed to develop a framework of appropriate methodologic approaches to be used in linked analyses across large cohorts.